THE MARKETING FEATURES OF THE TOURIST SERVICES PROMOTION - Ольга Буднік; Людмила Тарасович; Світлана Лавриненко (Економіка та суспільство, 2025)
The study is devoted to the determination of the main trends and the prospects of the domestic tourism market development, as well as the marketing communications using for the tourist services promotion under the today challenges conditions. It is suggested to pay attention to the certain types of tourism offering, in particular, green (ecological), sports, accessible tourism in order to strengthen the social component. It was determined that improving the competitive position in the tourist market is possible through the marketing promoting system applying. The necessity of the clear and the consistent algorithm developing for the target consumers is proposed and the necessity of their needs defining and meeting is indicated. The importance of the marketing communication tools differentiation, depending on the region of tourism activity, is emphasized. The significace of the personal and individual offers establishing is underlined.